Rather than Rs1800796 Polymorphism, Expression of Interleukin-6 is Associated with Disease Progression of Chronic HBV Infection in a Chinese Han Population. Issue 6 (25th November 2013) - Tang, Shengli; Liu, Zhisu; Zhang, Yongxi; He, Yueming; Pan, Dingyu; Liu, Yuanyuan; Liu, Quanyan; Zhang, Zhonglin; Yuan, Yufeng
Abstract : Interleukin-6 plays an important role in chronic inflammation as well as tumor growth and progression. Here, a case-control study was undertaken to investigate the association of rs1800796 polymorphism of IL-6 gene and serum levels with disease progression of chronic HBV infection. Rs1800796 polymorphism was genotyped in 641 Chinese Han patients with chronic HBV infection, including 23 IT, 25 IC, 292 CHB, 153 LC, and 148 HCC patients and 265 healthy controls. Serum IL-6 levels were measured in 23 IT, 25 IC, 47 CHB, 41 LC, and 49 HCC patients and 45 healthy controls, and the classifications of HCC were accorded to BCLC staging system. We found no significant association between rs1800796 polymorphism and disease progression of chronic HBV infection; however, serum IL-6 levels showed significant statistical differences between patients with CHB, LC, and HCC. Moreover, statistical differences can be observed in patients with terminal stage HCC compared with those of early to intermediate or advanced stage HCC. Our findings suggest that rs1800796 polymorphism unlikely contribute significantly to affect the progression of chronic HBV infection, and serum IL-6 levels can act as a useful indicator for disease progression and severity of chronic HBV infection.